1991
DOI: 10.1113/jphysiol.1991.sp018520
|View full text |Cite
|
Sign up to set email alerts
|

Secretagogue‐evoked changes in intracellular free magnesium concentrations in rat pancreatic acinar cells.

Abstract: SUMMARY1. This study employs the fluorescent dye Mag-Fura-2 acetoxymethyl ester (AM) to measure intracellular free magnesium concentration [Mg2+]i in isolated rat pancreatic acinar cells. Initially a number of protocols were investigated to develop optimal loading conditions for the dye Mag-Fura-2 AM. The procedure yielding cells which showed minimal dye loss and no adverse compartmentalization was adopted for subsequent experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The decrease revealed a dosedependency with secretagogues, and atropine blocked the ACh-evoked response. Control experiments indicated that the secretagogues-induced decrease can not be attributed to a bleaching effect caused by the excitation beam, which together with the dose-dependency and the effect of atropine confirms that the observed response is not artefactual (40). Different doses of adrenaline, noradrenaline and histamine were also examined, but no changes in [Mg 2+ ] i were seen (40,42 -mobilising agents such as ACh and CCK-8, it was decided to make this point clearer by co-loading either Fura-2 or Magfura-2 loaded cells with BAPTA-AM, a Ca 2+ chelator (46).…”
Section: Exocrine Pancreasmentioning
confidence: 56%
See 4 more Smart Citations
“…The decrease revealed a dosedependency with secretagogues, and atropine blocked the ACh-evoked response. Control experiments indicated that the secretagogues-induced decrease can not be attributed to a bleaching effect caused by the excitation beam, which together with the dose-dependency and the effect of atropine confirms that the observed response is not artefactual (40). Different doses of adrenaline, noradrenaline and histamine were also examined, but no changes in [Mg 2+ ] i were seen (40,42 -mobilising agents such as ACh and CCK-8, it was decided to make this point clearer by co-loading either Fura-2 or Magfura-2 loaded cells with BAPTA-AM, a Ca 2+ chelator (46).…”
Section: Exocrine Pancreasmentioning
confidence: 56%
“…Control experiments indicated that the secretagogues-induced decrease can not be attributed to a bleaching effect caused by the excitation beam, which together with the dose-dependency and the effect of atropine confirms that the observed response is not artefactual (40). Different doses of adrenaline, noradrenaline and histamine were also examined, but no changes in [Mg 2+ ] i were seen (40,42 -mobilising agents such as ACh and CCK-8, it was decided to make this point clearer by co-loading either Fura-2 or Magfura-2 loaded cells with BAPTA-AM, a Ca 2+ chelator (46). At a BAPTA concentration equal to 10 µM, which enabled a small rise in [Ca 2+ ] i , not enough to interfere with Magfura, the typical decrease in [Mg 2+ ] i was found after the addition of CCK-8 but the initial rise was no longer present, indicating that it was an artifact.…”
Section: Exocrine Pancreasmentioning
confidence: 56%
See 3 more Smart Citations